A cross-sectional study on heart rate variability and subjective recovery to optimise performance - Higgins, P.; O'Donovan, A.; Hayes, O.; Doherty, R.; Daly, A.; Crognale, D. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Heart rate variability (HRV) and psychological assessments are used to monitor the athlete`s response to training and their subsequent recovery status. However, the relationship between HRV and perceptions is not yet understood. The purpose of this cross-sectional study was to explore the associations between HRV and subjective measures of fatigue, recovery, and psychological state. METHODS: Twenty-five competitive endurance athletes (20.6 ± 2.06 yrs.) were examined in the morning (08:00 to 12:00) after a training session (>6 Rating of Perceived Exertion, > 60 minutes). Heart rate variability (lnRMSSD, pNN50) was determined through 5-minute electrocardiogram recording. The psychological assessments which indicate perceived recovery status were the Total Quality Recovery scale, Perceived Recovery Status scale, Hooper Index and Total Mood Disturbance Score. Pearson`s Correlation Coefficient was used to assess the associations between HRV and each of the four psychological assessments. Mean HRV was compared between athletes, when grouped according to recovery status, via the Total Quality Recovery (*13 or <13) and Perceived Recovery Status (>5 or <5) scales. RESULTS: A low positive correlation was found between the Total Quality Recovery score and lnRMSSD (r = 0.435, 95% CI = 0.048 - 0.708). Non-significant correlations were reported for all other relationships. A significant mean difference in lnRMSSD and pNN50 was found between athletes with different recovery states on both the Total Quality Recovery (MD = 0.7, 95% CI= 0.17 - 1.22; MD = 23.33, 95% CI= 4.46 - 42.19) and Perceived Recovery Status (MD=0.71, 95% CI= 0.21-1.22; MD = 23.99, 95% CI= 5.66 - 42.34) scales. CONCLUSION: Our findings suggest that there is a limited association between HRV and perceived recovery scores in endurance athletes. When grouped by recovery status, athletes exhibit differences in HRV. This study warrants further exploration of the relationship between HRV and subjective perceptions of fatigue.